2014
DOI: 10.1371/journal.pone.0097741
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Functionalization of a Calcium Phosphate-Coated Titanium Surface with Slow-Release Simvastatin and Metronidazole to Provide Antibacterial Activities and Pro-Osteodifferentiation Capabilities

Abstract: Coating the surface of titanium implants or other bone graft substitute materials with calcium phosphate (Ca-P) crystals is an effective way to enhance the osteoconduction of the implants. Ca-P coating alone cannot confer pro-osteodifferentiation and antibacterial capabilities on implants; however, it can serve as a carrier for biological agents which could improve the performance of implants and bone substitutes. Here, we constructed a novel, bi-functional Ca-P coating with combined pro-osteodifferentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…There, after two and four days the antimicrobial properties of the coating were lost. Analogously to our results, Norowski et al [13] confirmed a short term antibacterial effect of their implant coating. They evaluated a chitosan coating loaded with tetracycline and chlorhexidine and demonstrated that it can reduce the risk of infections for a short period of time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There, after two and four days the antimicrobial properties of the coating were lost. Analogously to our results, Norowski et al [13] confirmed a short term antibacterial effect of their implant coating. They evaluated a chitosan coating loaded with tetracycline and chlorhexidine and demonstrated that it can reduce the risk of infections for a short period of time.…”
Section: Discussionsupporting
confidence: 92%
“…In front of this problem numerous studies have focused on the development of drug releasing implant coatings for the prevention of bacterial adhesion [13], [16], [18], [19] and subsequent biofiom formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, utilizing both scaffolds and other dental-differentiation supplementary materials has been investigated in recent researches. 16,[19][20][21] The ideal cell resource for tissue engineering should be proliferative enough, non-immunogenic, and have the ability to differentiate into desired functional cells. Therefore adult stem cells in particular, MSCs isolated from either bone marrow or other origins have shown promising outcomes in regenerative medicine and cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…MTZ is an antibiotic specific to the Gram-negative anaerobic bacteria 11 and is widely used to support dentoalveolar regeneration. 10,12,13 In addition, we incorporated platelet-derived growth factor (PDGF), a potent mitogen and chemoattractant, 14 in the nanofibers on the inner surface to facilitate the healing and regeneration process. We assessed the biocompatibility and applicability of this FGM design in a cell-based system and in rodent models.…”
mentioning
confidence: 99%